Additional notes on lichens of the Prince Olav Coast, Antarctica - Kashiwadani, Hiroyuki (1979)
P(論文) Four species of lichens are reported as new to the Prince Olav Coast, Antarctica. They are Biatorella cerebriformis (DODGE) FILS., Caloplaca athallina DARB., Caloplaca citrina (HOFFM.) TH. FR., and Xanthoria parietina (L.) BELTR. Of these, X. parietina is new to the antarctic flora. An unknown chemical substance is found in Acarospora gwynii DODGE & RUD., an endemic species in Antarctica. departmental bulletin paper